PERAN TRUST DALAM MEMEDIASI PENGARUH PERCEIVED EASE OF USE DAN PERCEIVED USEFULNESS TERHADAP REPURCHASE INTENTION PADA APLIKASI TOKOPEDIA - Meisa Alvioni Syamsudin; Leni Evangalista Marliani (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to analyze the role of trust in mediating the effect of perceived ease of use and perceived usefulness on repurchase intention on the Tokopedia application. The population in this study are Tokopedia users who live in Bandung City. The sample was taken using purposive sampling technique with the criteria that respondents 17-64 years old who have made at least two transactions in the Tokopedia application. The number of samples in this study amounted to 120 respondents. Data were collected through an online questionnaire based on a 5-point Likert Scale and analyzed using multiple regression and the sobel test. The results showed that perceived ease of use and perceived usefulness have a positive effect on trust. Perceived ease of use, perceived usefulness, trust a positive effect on repurchase intention. The sobel test indicates that trust is able to mediate the influence between perceived ease of use and perceived usefulness on repurchase intention. This research provides important insights for the development of e-commerce strategies in increasing customer repurchase intention.